شعر الصعاليك: نظرة في الرؤية والأداة - القحطاني، مذكر بن ناصر (جامعة الأزهر - کلیة اللغة العربیة بالمنوفیة, 2022)
يتناول هذا البحث بالدراسة الرؤى والأدوات التي يتميز بها شعر الصعاليك بوصفه مكونا مختلفا من بقية الأنماط الشعرية التي كانت موجودة في تلك الفترة، وبوصفه ثورة على النص الجاهلي القديم سواء على مستوى الشكل أو المحتوى، وقدمت هذه الدراسة الكثير من الدلالات والسمات لعدد من القراءات التجديدة لعتبات النص للقصيدة الصعلوكية من خلال إبراز السردية في شعرهم، ورصد أهم السمات الأسلوبية لهذا النص المختلف. وهي-بعد- قراءة منفحته على النص ذاته دون ارتباط بالقراءة التاريخية أو التعاقبية للنصوص التي جعلت منها إطارا أو قالبا واحدا غير مختلف لجميع نصوص تلك المرحلة الزمنية، فالقراءة التاريخية قد لا يلحظها القارئ في هذا البحث؛ لأنها تهدف في الأساس إلى سبر المضمون والإطار معا، وفق قراءة تكاملية تستشرف آفاق النص الشعري مستفيدة من القراءات السابقة التي تتقاطع معها، بهدف الوصول إلى نتائج مختلفة عن الدراسات السابقة. وانتظمت تلك الدراسة في مقدمة وتمهيد وثلاث مباحث، وخاتمة أكدت على أن النص الصعلوكي لم يلتزم بالبدايات الكلاسيكية للقصيدة الجاهلية، وتموضع اهتمامه بالوحدة الموضوعية التي ظهرت في شعرهم بصورة لافتة، واعتبرت القصيدة الصعلوكية مصدرا معجميا لصانعي المعجم والدلالة الأول لأن لغتهم تنطلق من شعور خاص يغلب عليه التمرد والثورة وعدم التماهي مع هو طبيعي في وقتهم، والقصيدة الصعلوكية صورة صادقة للشاعر الجاهلي المتمرد. This research deals with the study of the visions and tools that characterize the poetry of tramps as a different component from the rest of the poetic styles that existed in that period, and as a revolution against the ancient pre-Islamic text, whether at the level of form or content. The text of the tramp poem by highlighting the narration in their poetry, and monitoring the most important stylistic features of this different text. It is - after - a reading open to the text itself without linking to the historical or successive reading of the texts that made them a single frame or template that is not different for all the texts of that time period. The historical reading may not be noticed by the reader in this research; Because it mainly aims to probe the content and the framework together, according to an integrative reading that foresee the horizons of the poetic text, taking advantage of the previous readings that intersect with it, with the aim of reaching different results from previous studies. That study was organized into an introduction, a preface, three chapters, and a conclusion that confirmed that the tramp based text did not adhere to the classical beginnings of the pre-Islamic poem, and focused its attention on the objective unity that appeared in their poetry in a remarkable way. The tramp poem was considered a lexical source for the makers of the first lexicon and semantics because their language stems from a special feeling dominated by rebellion, revolution and lack of identification with what is natural in their time, and the tramp poem is a true image of the rebellious pre-Islamic poet.
Keywords: شعر الصعاليك -- الأدب الجاهلي -- النقد الأدبي -- النصوص الأدبية